Research on component compatibility and aging behavior of chemically toughened high-performance asphalt - Huang, Bin; Wang, Chenxi; Yang, Yi; Wang, Yuchen; Zhao, Yanan; Jiang, Ruiyao (Frontiers in Built Environment, 2025)
IntroductionFrequent cracks, potholes, and other defects, as well as a decline in the durability of asphalt pavements, are specific manifestations of the deterioration of road performance caused by asphalt aging. The compatibility between different oil-source asphalts and green high-viscosity modifiers critically determines the performance and aging resistance of modified asphalt materials.MethodsThis study systematically investigated three representative oilsource asphalts (noted as BA-A, BA-B, BA-C) combined with a novel green high-viscosity modifier to prepare chemically toughened high-performance asphalts (noted as HP-A, HP-B, HP-C). The research employed comprehensive analytical methods, including physical property characterization, dynamic shear rheometry, Fourier transform infrared spectroscopy, and gel permeation chromatography, to evaluate compatibility mechanisms and aging behavior under both short-term aging (using thin-film oven test) and long-term (using pressure aging vessel) aging conditions.ResultsThe green highviscosity modifier exhibits optimal compatibility with BA-C asphalt, displaying elevated softening point and Brookfield viscosity with superior resistance to shear deformation, making it particularly suitable for high-temperature applications in high-temperature regions and heavy-duty traffic pavements. Under short-term aging condition, HP-A asphalt has the minimal softening point increment of 0.4°C, while HP-C asphalt has the lowest viscosity aging index of 2.6%. Under long-term aging, HP-C asphalt has the lowest softening point increment and viscosity aging index of 4.2°C and 6.1%, respectively, indicating good long-term aging resistance. Molecular analysis reveals that SBS modified asphalt and HP-B asphalt show increased molecular weight distribution ratios due to oxidative crosslinking, whereas HP-A and HP-C asphalts show decreased ratios due to chain segment fracture. HP-B asphalt has the highest sulfoxide aging index increase due to elevated sulfur content, while HP-C asphalt shows superior antioxidant properties with lower carbonyl and sulfoxide aging indices, 43.2% and 36.6%, respectively, attributed to its high aromatic content. And proposed using two crack characteristic parameters, fractal dimension and crack rate, to describe the extension characteristics of cracks. The results indicate that the road surface is more prone to cracking in negative zero temperature environments, with the number and rate of cracks generated at −15°C being much higher than the other three low-temperature environments. Compared to the 15°C environment, the crack rate increased by 18.26%.DiscussionIt has been confirmed that BA-C asphalt has excellent compatibility with green high-viscosity modifiers, which are ideal for use in high-temperature regions and heavy-duty traffic pavements, offering significant improvements in pavement high-temperature stability and long-term durability.